SMACK+Corral: A Modular Verifier (Competition Contribution) - Haran, Arvind; Carter, Montgomery; Emmi, Michael; Lal, Akash; Qadeer, Shaz; Rakamaric, Zvonimir (Tools and Algorithms for the Construction and Analysis of Systems (TACAS), 2015)
SMACK and Corral are two components of a modular toolchain for verifying C programs. Together they exploit state-of-the-art compiler technologies and theorem provers to simplify and dispatch verification conditions.